So famous and so gay : the fabulous potency of Truman Capote and Gertrude Stein - Solomon, Jeff, 1968- (University of Minnesota Press, 2017)
"Gertrude Stein (1874-1946) and Truman Capote (1924-1984) should not have been famous. They made their names between the Oscar Wilde trial and Stonewall, when homosexuality meant criminality and perversion. And yet both Stein and Capote, openly and exclusively gay, built their outsize reputations on works that directly featured homosexuality and a queer aesthetic. How did these writers become mass-market celebrities while other gay public figures were closeted or censored? And what did their fame mean for queer writers and readers, and for the culture in general? Jeff Solomon explores these questions in So Famous and So Gay. Celebrating lesbian partnership, The Autobiography of Alice B. Toklas was published in 1933 and rocketed Stein, the Jewish lesbian intellectual avant-garde American expatriate, to international stardom and a mass-market readership. Fifteen years later, when Capote published Other Voices, Other Rooms, a novel of explicit homosexual sex and love, his fame itself became famous. Through original archival research, Solomon traces the construction and impact of the writers' public personae from a gay-affirmative perspective. He historically situates author photos, celebrity gossip, and other ephemera to explain how Stein and Capote expressed homosexuality and negotiated homophobia through the fleeting depiction of what could not be directly written--maneuvers that other gay writers such as Gore Vidal, Tennessee Williams, and James Baldwin could not manage at the time. Finally So Famous and So Gay reveals what Capote's and Stein's debuts, Other Voices, Other Rooms and Three Lives, held for queer readers in terms of gay identity and psychology--and for gay authors who wrote in their wake"--